(untitled) (Global Journal of Management and Business Research, 2020)
Kuwait is mentioned as one of multi-national workplaces. It is important to identify motivating factors that affect the workers in Kuwait construction workplaces. Maslow’s hierarchy is the most common theory of motivation. Many studies investigated the application of Maslow’s hierarchy in many places around the world. This study surveyed the motivational needs of employees working in the construction industry in Kuwait. A questionnaire designed to evaluate the motivation needs of employees for different public and private sector in Kuwait industry.